2014
DOI: 10.1637/10588-061013-case.1
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Proventricular Dilatation Disease in Captive Native Psittacines in Brazil

Abstract: An outbreak of proventricular dilatation disease (PDD), a fatal inflammatory disease of psittacines (Aves: Psittaciformes), is described in native Brazilian psittacines. Twenty captive psittacines that died of suspected PDD were necropsied and 10 were submitted to histopathology, reverse transcriptase PCR (RT-PCR), and immunohistochemistry (IHC) for avian bornavirus (ABV). Examined species were one pileated parrot (Pionopsitta pileata), three vinaceous-breasted parrots (Amazona vinacea), two blue-winged macaws… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
1
17
0
2
Order By: Relevance
“…Fewer exotic species such as Australian ringnecks (Barnadius zonarius), cockatiels (Nymphicus hollandicus), African grey parrots (Psittacus erithacus), and umbrella cockatoos (Cacatua alba) have been reported as positive. These birds were originated from breeding facilities, clinics, or rehabilitation centers from the states of Sao Paulo, Rio de Janeiro, Mato Grosso do Sul and Minas Gerais (Donatti et al 2014, Encinas-Nagel et al 2014, Philadelpho et al 2014. Although one of these studies reported PaBV infection or PDD signs in free-ranging psittacines (Encinas-Nagel et al 2014), these birds were kept in captivity after rescue or confiscation by environmental authorities, and information about how long these animals were kept in these facilities and their status prior captivity are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fewer exotic species such as Australian ringnecks (Barnadius zonarius), cockatiels (Nymphicus hollandicus), African grey parrots (Psittacus erithacus), and umbrella cockatoos (Cacatua alba) have been reported as positive. These birds were originated from breeding facilities, clinics, or rehabilitation centers from the states of Sao Paulo, Rio de Janeiro, Mato Grosso do Sul and Minas Gerais (Donatti et al 2014, Encinas-Nagel et al 2014, Philadelpho et al 2014. Although one of these studies reported PaBV infection or PDD signs in free-ranging psittacines (Encinas-Nagel et al 2014), these birds were kept in captivity after rescue or confiscation by environmental authorities, and information about how long these animals were kept in these facilities and their status prior captivity are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Proventricular dilatation disease (PDD) is a lethal and important disease of captive psittacine birds, affects a wide Proventricular dilatation disease (PDD) outbreak in blue-and-gold macaws (Ara ararauna) in the State of Santa Catarina, southern Brazil 1 range of species, including several endangered species,and lacks an effective treatment (Staeheli et al 2010, Wyss et al 2009. PDD has been identified worldwide, in North America, Europe, Asia, Africa (Hoppes et al 2010), and South America, including Brazil (Donatti et al 2014, Encinas-Nagel et al 2014, Philadelpho et al 2014. PDD is caused by Psittaciform 1 bornavirus (PaBV), a non-segment single stranded, negative sense virus of the order Mononegavirales (Honkavuori et al 2008, Kistler et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although some of these ABV have been able to induce clinical disease and characteristic lesions, several aspects of PDD pathogenesis are still not elucidated. Even though the epidemiological studies of parrot bornavirus have increased substantially in different parts of the world in recent years, few studies have been conducted in captive psittacine in Brazil [16][17][18]. Nevertheless, PDD has already been described in Brazilian threatened species, such as Spix's macaw (Cyanopsitta spixii), extinct in the wild [19].…”
Section: Introductionmentioning
confidence: 99%
“…Com a recente observação da diferença na apresentação da doença em relação ao genótipo PIEPENBRING et al, 2016) -GONÇALVES et al, 2009;WEISSEMBOCK et al, 2009a;RUBBENSTROTH et al, 2012;DONATTI et al, 2013). A primeira amostra de genótipo 4 pertencia a uma Cacatua alba, importada da América do Norte que havia viajado entre Brasil e Estados Unidos pelo menos duas vezes, indicando uma possibilidade de ter sido infectada fora do país.…”
Section: Detecção De Poliomavírus Em Canáriosunclassified
“…No Brasil, o bornavírus foi descrito apenas em psitacídeos de cativeiro (MARIETTO-GONÇALVES et al, 2009;DONATTI et al, 2013), entretanto, não há estudos descritos em aves de vida livre nem a pesquisa viral em outros gêneros.…”
Section: Introductionunclassified